Dampak Upah Minimum terhadap Employment: Pendekatan Difference in Spatial Difference - Ardhian Kurniawati (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2018)
Most studies on the impact of minimum wages on employment resulted in a negative impact of minimum wages on employment in the formal sector. However, there are indications of bias because the results of these studies assume that the labor market between observation units are independent, whereas the labor market between observation units are dependent on each other. This study aims to estimate the impact of minimum wages on employment considering that between observation units are dependent on each other. Using a difference in spatial difference this study estimate the impact of minimum wages on employment using data Sakernas year 2010-2015 in Java. The estimation results a positive impact of the increase in the minimum wage on employment in the formal sector and negatif impact on employment in the informal sector. 100% increase in the real minimum wage is assosiate with approximately a 0.41%-0.47% increase in employment in the formal and decrease employment in informal sector approximately 0.22%-0.35%.